Upsize your word power [soundrecording] - Funk, Peter; Funk, Mary.; Huber, Sherry; Ruben, Paul. (1998)
A guide in expanding vocabulary especially on the use of synonyms.
Read by Peter Funk.
Keywords: Vocabulary; Language